Guidelines for Video Capsule Endoscopy: Emphasis on Crohn's Disease - Park, Soo-Kyung (Clin Endosc, 2015)
Video capsule endoscopy (VCE) is an ingestible video camera that transmits high-quality images of the small intestinal mucosa. This makes the small intestine more readily accessible to physicians investigating the presence of small bowel disorders, such as Crohn's disease (CD). Although VCE is frequently performed in Korea, there are no evidence-based guidelines on the appropriate use of VCE in the diagnosis of CD. To provide accurate information and suggest correct testing approaches for small bowel diseases, the Korean Gut Image Study Group, part of the Korean Society of Gastrointestinal Endoscopy, developed guidelines on VCE. Teams were set up to develop guidelines on VCE. Four areas were selected: diagnosis of obscure gastrointestinal bleeding, small bowel preparation for VCE, diagnosis of CD, and diagnosis of small bowel tumors. Three key questions were selected regarding the role of VCE in CD. In preparing these guidelines, a systematic literature search, evaluation, selection, and meta-analysis were performed. After writing a draft of the guidelines, the opinions of various experts were solicited before producing the final document. These guidelines are expected to play a role in the diagnosis of CD. They will need to be updated as new data and evidence become available.